(untitled) (Indian Journal of Public Health Research & Development, 2020)
We present a case of clinically extensive bilateral DVTs associated with chronic total inferior vena cava thrombosis with underlying crohn’s disease and who is on steroid therapy. Young patients presenting with symptoms of DVT should be investigated not only to establish any thrombophilic pre-disposition but to ascertain the proximal extent of thrombus which may itself influence treatment. Treatment options in the case of IVC thrombus without anatomical variance include anticoagulation, mechanical thrombectomy, systemic thrombolytic therapy, transcatheter regional thrombolysis, and angioplasty